Features of the mineralogical composition of technogenic soils of coal dumps in Kuzbass, Kemerovo Region, Russia - D. E. Kolpakova; I. S. Milentieva; L. K. Asyakina; N. V. Fotina; A. Yu. Prosekov (Юг России: экология, развитие, 2024)
Study of the mineralogical composition of soils in coal dumps formed in sectors of the Kemerovo region for further remediation of posttechnogenic landscapes.Samples of technogenically disturbed soils of the Mokhov, Korchakol and Barzas dumps located on the territory of the Kemerovo region were studied. The results were obtained using X‐ray diffraction analysis.The chemical composition of the soils of the Mokhovsky, Barzassky and Korchakolsky coal dumps have been determined. Chromium pyrophosphate (Cr2O7Р2), aluminium sulfphide (Al2S3) and zirconium silicide (ZrSi) prevail in the samples of the Mokhov dump, while the Barzas dump contains a significant amount of carbon (C), strontium zirconate (SrZrO3) and calcium carbonate (CaCO3).Based on these results, conclusions were drawn about the structure and some physical and chemical parameters of the soil.